ANALISIS STANDAR PENDIDIK DAN TENAGA KEPENDIDIKAN DI SMPN 2 KEDUNGWARINGIN - Safana Hani Hamidah; Laitsa Nailul Amani; Hisa Fakhriya; Muhammad Dzaky; Hinggil Permana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Educator and education personnel standards are an important component of national education standards that aim to ensure the quality of learning in schools. Educators are required to have pedagogical, professional, social, and personal competencies in order to carry out their role as educators and role models for students. Meanwhile, education personnel function to support the administrative, managerial, and technical aspects that support the learning process. The implementation of these standards encourages increased professionalism through certification programs, ongoing training, and regular performance evaluations. With the existence of standards for educators and educational personnel, the quality of education is expected to be more assured, the learning atmosphere will be more conducive, and national education goals can be achieved. In addition, the implementation of these standards also emphasizes that the success of education does not only depend on teachers in the classroom, but also on educational personnel who ensure that educational services run effectively.